2023
DOI: 10.1039/d2nr04598b
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fixation methods for SEM analysis of self-assembling peptide hydrogel nanoarchitecture

Abstract: SEM preparation techniques for self-assembling peptide hydrogels can have dramatic influence on apparent structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The supramolecular fibrillar elements are also characterized by a right-handed twisting. This mutual entanglement of fibers is typically observed for peptide-based hydrogels [50].…”
Section: Sem Characterizationmentioning
confidence: 59%
“…The supramolecular fibrillar elements are also characterized by a right-handed twisting. This mutual entanglement of fibers is typically observed for peptide-based hydrogels [50].…”
Section: Sem Characterizationmentioning
confidence: 59%
“…SEM demonstrated that the diluted gels exhibited a filamentary structure consisting of nanofibers with diameters of approximately 40-60 nm. These morphological features all indicated that multiple fibers with lengths greater than 600 nm were entangled with each other to produce a three-dimensional network structure, i.e., a macroscopic gel [30,31]. It was also observed that there was a dense interweaving of nanofibers in these undiluted three-dimensional networks, particularly in hydrogels at pH 5.0.…”
Section: Hydrogel Preparationmentioning
confidence: 93%
“…1). 8,34,38,41 Cell culture Human bone marrow-derived mesenchymal stem cells (MSCs) purchased from the Tulane Center for Stem Cell Research and Regenerative Medicine (Tulane University, New Orleans, LA, USA) and characterised as previously reported. 46 MSCs were cultured in a media consisting of α-minimum essential media (αMEM; Invitrogen) supplemented with 16.5% foetal bovine serum (FBS; GIBCO), 2 mM L-glutamine, 100 U mL −1 penicillin and 100 μg mL −1 streptomycin (all from Invitrogen), according to the Tulane Center for Gene Therapy Protocol for expansion of Human MSCs.…”
Section: Methodsmentioning
confidence: 99%
“…Lipidated peptides with cell penetrating properties can be applied to direct peptide drugs, or other cargo, to specific subcellular regions, such as the mitochondrial membrane 28 in targeted cancer treatments. [29][30][31][32] Our laboratory has developed self-assembling peptide hydrogels for a range of applications including 2D cell culture, 8,9,[33][34][35][36][37][38] cellular guidance 36 and drug delivery. 9 Fibres are generated from the hierarchical self-assembly of N-acetylated β 3 -peptides 39,40 and functionalisation with a lipid promotes hydrogelation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation